Effect of the COVID-19 Pandemic on the Diagnosis of Non-Melanoma Skin Cancers: A Retrospective Case Control Study - Yuksel, Esma Inan; Cicek, Demet; Demir, Betul; Calik, Ilknur; Canat, Dilek (OrtadogÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S., 2022)
Objective: The coronavirus disease-2019 (COVID-19) pandemic has caused delays in the diagnosis and treatment of some oncological diseases. This study aimed to reveal the effect of the COVID-19 pandemic on the frequency of diagnosis of non-melanoma skin cancers (NMSC) and the demographic characteristics of patients. Material and Methods: Patients aged over 18 years, who were histopathologically diagnosed with basal cell carcinoma (BCC) or squamous cell carcinoma (SCC) between March 12, 2019 and March 11, 2021 were included in the study. The demographic characteristics of these patients, the number of total skin biopsies, and the number of BCC and SCC biopsies were compared between the pre-pandemic and pandemic periods, based on the date of March 12, 2020, when the pandemic measures began to be implemented in Turkey. Results: With the pandemic, there was a 26.7% decrease in the total skin biopsies and a 21% decrease in the total NMSC biopsies. Despite a 34% decrease in the number of biopsies for the diagnosis of BCC, a 15.8% increase was observed in the number of biopsies for the diagnosis of SCC. The frequency of excisional biopsies was observed to increase among the patients with BCC and SCC during the pandemic period (p=0.004 and p=0.001, respectively). Conclusion: The number of total skin biopsies and total NMSC biopsies significantly decreased during the pandemic period. The health system should be reorganized to effectively handle pandemics and similar crisis periods, and new strategies should be determined regarding patient education, early diagnosis, and treatment approaches for NMSC. © 2022 OrtadogÃ‚ÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S.. All rights reserved.
Keywords: Basal cell carcinoma; COVID-19; pandemics; skin neoplasms; squamous cell carcinoma